Research Results of the Potato Digger Technological Process - V. M. Alakin; G. S. Nikitin (Сельскохозяйственные машины и технологии)
A potato digger equipped with a fourbladed beater operating in connection with rotary separating surface has low material and energy consumption, higher separating efficiency, as well as lower degree of tuber damaging. The potato digger design should include a fourbladed intakeandfeed beater to prevent potato heap transportation faults in front of the first section. (Research purpose) Increasing the technological and economic efficiency of a potato diggingand separating unit through the determination of the optimum values of the design parameters and operating process of the intakeandfeed beater. (Materials and methods) the authors have made an overview of general principles of ensuring the stability of the potato heap movement provided by the fourbladed intakeandfeed beater. The dependency of the minimum beater speed on the operating speed of the potato digger has been found to exclude a probability of its overloading. The methodology of calculating the potato heap velocity and the cutoff angle between the material and the beater blades has been worked out by analyzing potato heap lifting to the upper points of the working units of the rotary separator’s first section. Operating speed of the beater has been determined through the differential equation for the speed of a potato heap moving along the blade surface. (Results and discussion) Preliminary potato heap speed and cutoff angle have been found through the equation of dynamics describing the projectile motion of an object thrown at an angle. The operating values of the angles are dependent on the potato digger working speed and can be selected from the triangle of speeds. The authors have determined the dependence of the optimal beater speed on the working speed of a potato digger. Its value should exceed the minimum speed of the beater. (Conclusions) Theoretical results allow proposing the best design features and optimum working process parameters of a fourbladed beater receiving a potato heap, transporting it and lifting on the rotary separating surface.